2020
DOI: 10.3390/ijms21186459
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-30a-3p Regulation of Oncogenic Targets in Pancreatic Ductal Adenocarcinoma Pathogenesis

Abstract: Our recent studies have implicated some passenger strands of miRNAs in the molecular pathogenesis of human cancers. Analysis of the microRNA (miRNA) expression signature in pancreatic ductal adenocarcinoma (PDAC) has shown that levels of miR-30a-3p, the passenger strand derived from pre-mir-30a, are significantly downregulated in PDAC tissues. This study aimed to identify the oncogenes closely involved in PDAC molecular pathogenesis under the regulation of miR-30a-3p. Ectopic expression assays showed that miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…ITGA2 has been reported to play a critical role in modulating the pancreatic cancer immune response by transcriptionally increasing the expression of PD-L1 in cancer cells (Ren et al, 2019). At the same time, it has been reported that ITGA2 is associated with unfavorable survival of PDAC patients by affecting the malignant biological behavior of pancreatic cancer cells (Rozengurt, Sinnett-Smith & Eibl, 2018;Shimomura et al, 2020;Yan et al, 2020). Considering that the mechanism of ITGA2 in PDAC has been studied partly, we focused on FN1 which has no mechanism study in PDAC for further study.…”
Section: Discussionmentioning
confidence: 99%
“…ITGA2 has been reported to play a critical role in modulating the pancreatic cancer immune response by transcriptionally increasing the expression of PD-L1 in cancer cells (Ren et al, 2019). At the same time, it has been reported that ITGA2 is associated with unfavorable survival of PDAC patients by affecting the malignant biological behavior of pancreatic cancer cells (Rozengurt, Sinnett-Smith & Eibl, 2018;Shimomura et al, 2020;Yan et al, 2020). Considering that the mechanism of ITGA2 in PDAC has been studied partly, we focused on FN1 which has no mechanism study in PDAC for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies show that some passenger miRNAs have a tumor suppressor function in cancer cells. (e.g., miR-148-5p, miR-145-3p, miR-143-5p, miR-30c-2-3p, and miR-30a-3p) [19,26,41,42]. Those miRNA duplexes and their target oncogenic genes are closely associated with cancer pathogenesis [19,26,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…(e.g., miR-148-5p, miR-145-3p, miR-143-5p, miR-30c-2-3p, and miR-30a-3p) [19,26,41,42]. Those miRNA duplexes and their target oncogenic genes are closely associated with cancer pathogenesis [19,26,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, hsa-miR-30d-3p has not been reported in asthma yet. Hsa-miR-30a-3p was reported to regulate the tumorigenesis in various cancer, such as gastric cancer (Wang et al, 2019b), lung adenocarcinoma (Wang et al, 2020), and pancreatic ductal adenocarcinoma (Shimomura et al, 2020). Li and others reported that hsa-miR-30a-3p regulates eosinophil activity through targeting CCR3 in asthma (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%